ANALISA IMPAK PADA DESAIN KARAKURI KAIZEN TROLLEY DAN RAK STATIK DUA TINGKAT DENGAN METODE FEA - Amat, Mohammad Azwar; Luthfi, Muhammad; Badruzzaman, Badruzzaman; Hidayatulloh, Deni (Universitas Sriwijaya, 2024)
Karakuri kaizen is an approach to improve the efficiency of the production process by utilizing simple mechanisms that rely on the principles of mechanics without external energy (such as electricity or pneumatics). In this study, the impact analysis on the critical part of the karakuri kaizen design uses analytical and simulation methods. Simulation methods are divided into motion study, stress, strain, displacement, and velocity analysis. Impact simulation on dynamic rack mechanical stopper and impact simulation on static rack stopper. The results of analytical calculations and simulations on the box speed show that there are similarities in the time value and final speed of the box before stopping. The results of the impact simulation show that in the mechanical stopper path (a) the bolt pretension factor is still in a neutralized condition so that its effect is more dominant than the load on the box, the max stress ranges from 550-560 MPa and the strain is at 0.0025-0.0029. While the stopper path (b) oscillates with a max stress ranging from 270-320 MPa and a strain is at 0.002-0.0026. The box speed after impact is much greater than the input speed, due to the absence of a damping system, and the mass multiplier on the stopper being too large.